Network architecture in the 5Gmobile systems - Hongyu XIANG; Xinran ZHANG; Zhuying PIAO; Mugen PENG (Dianxin kexue)
In ordeRtomeet the performance requirements of 5G networking such as huge traffic,large links,and ultra-low latency,the traditional wireless access network architecture for wide coverage and high capacity design needs to evolve.Firstly,combining the 5G vision and needs,the characteristics and importance of the 5G access network architecture were clarified.Then the design principle and specific composition of the 5G access network architecture was introduced from the perspectives of academia and industry,and the advantages and disadvantages were analyzed.Finally,the challenges of access network architecture and possible future development directions were discussed.